SYNTHESIS AND CHARACTERIZATION ANALYSIS OF FE3O4/SiO2 CORE SHELL - Cassia, Diva; Sugihartono, Iwan; Isnaeni, Isnaeni; Soewoto, Haswi Purwandanu; Alaih, Akhmad Futukhillah Fataba; Triyono, Djoko; Mohar, Rahmat Setiawan; Tiam, Tan Swee (Program Studi Fisika Universitas Negeri Jakarta, 2023)
Fe3O4/SiO2 core shell synthesis has been carried out, and its characteristics has been analyzed to be used as a photocatalyst using co-precipitation and sol-gel method. Fe3O4 is used as the core material to eliminate the difficulty of separating the photocatalyst powder from the solution medium, SiO2 is used to avoid oxidation by preventing the Fe3O4 core from coming into direct contact with the solution. The samples were then characterized using X-Ray Diffraction (XRD), Fourier Transform Infra-Red (FTIR), and Vibrating Sample Magnetometer (VSM). The XRD and FTIR results showed that the crystal structure and movement of the sample molecules matched the standard characteristics from previous studies. The VSM characterization results show that SiO2 succeeded in reducing the value of the magnetization of Fe3O4, which proves that Fe3O4 has been successfully coated by SiO2.